O estrategista brasileiro da micro, pequena e média empresa privada nacional - Nunes, Geraldo Sant'Anna (2009)
The leadership of American literature in the field of business strategy and its consequent influence on the scientific and entrepreneurial world in Brazil is a real fact. It's also true that the major theories in strategy, especially from the classic school, the oldest and most influent in this field, were originated from empirical studies in large ¿ if not giant ¿ companies, many of them currently present in Brazil. The micro, small and medium Brazilian companies, of well known social and economical importance to the country, and its strategists are certainly not inert to this knowledge, but it doesn¿t necessarily means it can be applied with success in such different context. Previous studies indicate that this strategist makes use of intuition and is not very friendly with bureaucratic controls, but, in reality, the profile of this Brazilian executive is still unknown. Naturally, we do not expect this profile to be static in time, but reactive to changes on business environment, especially with the current globalization process. This research, aiming at knowing the profile of the Brazilian strategist of micro, small and medium companies and through an intensive revision on strategy literature, has built a mathematical model by the use of factor analysis, that can be applied in future studies. A new typology to understand the strategic thinking of these leaders is proposed. The conclusion shows that, for the executives in this research, intuition is not predominant on their decisions. Although more rational than intuitive, they refuse the idea of being purely rational. Besides, in the strategy formation process, they tend to have a collective spirit rather than deciding alone and to believe in the importance of being formal, planning and registering their intentions.